Transforming Islamic Education: The Role of Bu Nyai in Madurese Pesantren Leadership - Azhari, Jalaludin Faruk (Potret Pemikiran, 2024)
This study examines the role of Bu Nyai Nusantara (BNN) in transforming Islamic education within pesantren (Islamic boarding schools) in Madura, Indonesia. Utilizing a qualitative, phenomenological approach, the research explores the challenges faced by female leaders in traditionally male-dominated institutions, the strategies they employ to navigate and transform gender roles, and their unique contributions to Islamic education and broader societal change. The study draws on theories of women's educational leadership, particularly the model proposed by Grogan and Shakeshaft (2010), and Islamic feminism to analyze the experiences of Bu Nyai. Data was collected through in-depth interviews, participant observation, and document analysis across four districts in Madura. The findings reveal that Bu Nyai faces multifaceted challenges stemming from cultural norms, religious interpretations, and societal expectations. However, they have developed innovative strategies, including pursuing higher education, embracing technology, and building collaborative networks, to overcome these obstacles. The research highlights Bu Nyai's significant contributions to modernizing Islamic education, redefining religious authority, and advancing gender equality. Their leadership approach aligns with Grogan and Shakeshaft's five dimensions: leadership for change, instructional leadership, spiritual leadership, relational leadership, and balanced leadership. This study contributes to the understanding of women's leadership in religious educational contexts and demonstrates how educational leadership theories can be applied and adapted in diverse cultural settings. The findings have implications for educational policies and practices in Islamic institutions and provide insights into the potential of women's leadership as a catalyst for social change in traditional religious contexts.